Biodiesel production from camelina oil: Present status and future perspectives - Olivera S. Stamenković; Kshipra Gautam; Sneh L. Singla‐Pareek; Om P. Dhankher; Ivica G. Djalović; Milan D. Kostić; Petar M. Mitrović; Ashwani Pareek; Vlada B. Veljković (Food and Energy Security, 2023)
Abstract Camelina sativa (L.) Crantz is an oilseed crop with favorable potentials for biodiesel production, such as the high plant yield, high oil content in the seed, high net energy ratio, and low oil production cost. This review paper deals with the present state and perspectives of biodiesel production from camelina oil. First, important issues of camelina seed pretreatment and biodiesel production are reviewed. Emphasis is given to different biodiesel technologies that have been used so far worldwide, the economic assessment of the camelina oil biodiesel (COB) production, the camelina‐based biorefineries for the integrated biodiesel production, the COB life cycle analysis, and impact human health and ecosystem. Finally, the perspectives of COB production from the techno‐economic and especially genetic engineering points of view are discussed.